Future Directions for American Labor and Human Resources Policy - Kochan, Thomas; McKersie, Robert (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1989)
This paper discusses four commonly debated approaches toAmerican labor and human resource policy and argues for themost ambitious of these.